Scientific and methodological approaches to land management for organization of organic farming in Ukraine - Dorosh, O.; Svyrydova, L.; Svyrydov, O. (Land Management, Cadastre and Land Monitoring, 2025)
The study focused on scientific and methodological approaches to land management in the context of organizing organic agriculture in Ukraine. Particular attention is paid to the formation of a systematic approach to ecologically balanced land use and its harmonization with the requirements for certification of organic products according to international standards, in particular, the regulations of the European Union. The author identifies the components of land management, including: selection of suitable land plots in compliance with environmental safety criteria; creation of buffer zones to prevent pollution from the outside; minimization of the impact of neighbouring farms engaged in traditional agriculture; spatial zoning; rational placement of crops and livestock facilities. Approaches to the formation of crop rotations based on scientifically based crop rotation, the use of perennial grasses and green manure crops to restore soil fertility and improve the ecological balance within an organic farm are considered. Particular attention is paid to the use of innovative technologies, such as geographic information systems and remote monitoring, which contribute to the efficiency of management decisions. The author substantiates the importance of continuous monitoring of soil conditions, compliance with environmental standards, certification and implementation of product origin tracking systems as a prerequisite for transparency and quality assurance. Key words: organic agriculture, land management, land use organization, soil protection, environmental safety, sustainable development, certification of organic products, buffer zones.